The Formation of Prosociality: Causal Evidence on the Role of Social Environment - Fabian Kosse; Thomas Deckers; Pia Pinger; Hannah Schildberg-Hörisch; Armin Falk (Center for Economic Studies and ifo Institute (CESifo), 2018)
This study presents descriptive and causal evidence on the role of social environment for the formation of prosociality. In a first step, we show that socioeconomic status (SES) as well as the intensity of mother-child interaction and mothers' prosocial attitudes are systematically related to elementary school children's prosociality. In a second step, we present evidence on a randomly-assigned variation of the social environment, providing children with a mentor for the duration of one year. Our data include a two-year follow-up and reveal a significant and persistent increase in prosociality in the treatment relative to the control group. Moreover, enriching the social environment bears the potential to close the observed gap in prosociality between low and high SES children. A mediation analysis of the observed treatment effect suggests that prosociality develops in response to stimuli in the form of prosocial role models and intense social interactions.
Keywords: D64; C90; 330; formation of preferences; prosociality; social preferences; trust; social inequality